CLINICAL AND RADIOGRAPHIC MANIFESTATIONS OF GENERALIZED PERIODONTITIS IN PATIENTS ON THE BACKGROUND OF THE DAMAGE OF CERVICAL INTERVERTEBRAL DISCS - Valentyna М. Kulygina; Tamara O. Tepla; Olga Yu. Pylypiuk; Anastasiya V. Povshenyk; Maryna A. Goray (Eastern Ukrainian Medical Journal, 2022)
Introduction. In recent years, more and more attention has been paid to the study of the relationship between inflammatory processes in the periodontium and somatic diseases. Systemic processes, in particular, dystrophic lesions of the spine are known to have a significant role, leading to profound changes in the internal environment of the body and structural lesions of the periodontal tissues. The peculiarities of the clinical course of periodontal disease in patients with predominant damage of the cervical intervertebral discs are insufficiently described in the literature and remain relevant. The aim of this work was to study the features of clinical and radiographic indicators of periodontal tissues condition in patients with concomitant lesions of the intervertebral discs of the cervical spine. Materials and methods. Clinical and X-ray examination of 74 patients with the damage of cervical intervertebral discs was carried out: 48 persons of late mature age with stage I chronic generalized periodontitis and 26 elderly patients with stage II–III chronic generalized periodontitis. 40 patients of similar age groups and identical periodontal lesions without comorbidities comprised the control group. Research results. When comparing the clinical symptoms of chronic generalized periodontitis in groups of patients with damage of the intervertebral discs of the cervical spine and without somatic pathology, we revealed: increasing the depth of periodontal pockets and recession of the gums by 12.6% and 34.2% in late mature age subjects and by 10.2% and 16.2% in the elderly; the bleeding index by 19.4% in late mature age subjects and by 38.3% in the elderly; the intensity of exudation from periodontal pockets by 30.3% and 13.5%, respectively, with a high significant difference (p < 0.001). The indicators of furcation in the horizontal and vertical directions according to Tarnow–Fletcher and Hamp, respectively, were also worse in patients with damage of the cervical intervertebral discs. In addition, there was a decrease in the percentage of patients with an initial degree of bone resorption and an increase – with a high degree of bone loss. Conclusions. The clinical and radiographic study of patients revealed a negative impact of dystrophic lesions of the cervical spine on the clinical course of periodontal diseases, its deepening and burdening.